Rauwolfia polysaccharide can inhibit the progress of ulcerative colitis through NOS2-mediated JAK2/STAT3 pathway - Wu, Haidong; Jiang, Fan; Yuan, Wei; Zhao, Ye; Liu, Ning; Miao, Xinpu (PloS one, 2024)
Ulcerative colitis (UC) is an inflammatory disease of the digestive tract. Rauwolfia polysaccharide (Rau) has therapeutic effects on colitis in mice, but its mechanism of action needs to be further clarified. In the study, we explored the effect of Rau on the UC cell model induced by Lipopolysaccharide (LPS). We constructed a UC cell model by stimulating HT-29 cells with LPS. Dextran sodium sulfate (DSS) was used to induce mice to construct an animal model of UC. Subsequently, we performed Rau administration on the UC cell model. Then, the therapeutic effect of Rau on UC cell model and was validated through methods such as Cell Counting Kit-8 (CCK8), Muse, Quantitative real‑time polymerase chain reaction (RT-qPCR), Western blotting, and Enzyme-linked immunosorbent assay (ELISA). The results showed that Rau can promote the proliferation and inhibit the apoptosis of the HT-29 cells-induced by LPS. Moreover, we observed that Rau can inhibit the expression of NOS2/JAK2/STAT3 in LPS-induced HT-29 cells. To further explore the role of NOS2 in UC progression, we used siRNA technology to knock down NOS2 and search for its mechanism in UC. The results illustrated that NOS2 knockdown can promote proliferation and inhibit the apoptosis of LPS-induced HT-29 cells by JAK2/STAT3 pathway. In addition, in vitro and in vivo experiments, we observed that the activation of the JAK2/STAT3 pathway can inhibit the effect of Rau on DSS-induced UC model. In short, Rauwolfia polysaccharide can inhibit the progress of ulcerative colitis through NOS2-mediated JAK2/STAT3 pathway. This study provides a theoretical clue for the treatment of UC by Rau.